The effect of signal duration on the underwater hearing thresholds of two harbor seals (Phoca vitulina) for single tonal signals between 0.2 and 40 kHz: - Kastelein, R.A.; Hoek, L.; Wensveen, P.J.; Terhune, J.M.; Jong, C.A.F. de (2010)
The underwater hearing sensitivities of two 2-year-old female harbor seals were quantified in a pool built for acoustic research by using a behavioral psycho-acoustic technique. The animals were trained only to respond when they detected an acoustic signal (“go/no-go” response). Detection thresholds were obtained for pure tone signals (frequencies: 0.2–40 kHz; durations: 0.5–5000 ms, depending on the frequency; 59 frequency-duration combinations). Detection thresholds were quantified by varying the signal amplitude by the 1-up, 1-down staircase method, and were defined as the stimulus levels, resulting in a 50% detection rate. The hearing thresholds of the two seals were similar for all frequencies except for 40 kHz, for which the thresholds differed by, on average, 3.7 dB. There was an inverse relationship between the time constant (τ), derived from an exponential model of temporal integration, and the frequency [log(τ) = 2.86−0.94 log(f);τ in ms and f in kHz]. Similarly, the thresholds increased when the pulse was shorter than ∼ 780 cycles (independent of the frequency). For pulses shorter than the integration time, the thresholds increased by 9–16 dB per decade reduction in the duration or number of cycles in the pulse. The results of this study suggest that most published hearing thresholds ≤ 1 kHz for harbor seals are probably not absolute, as they were derived from signals with durations shorter than the time constants for those frequencies.